A novel method for transmission electron microscopy study of cytoplasmic fragments from preimplantation human embryos. Issue 6 (26th March 2016) - Halvaei, Iman; Khalili, Mohammad Ali; Nottola, Stefania A.
ABSTRACT: Transmission electron microscopy (TEM) is the main tool for exploring the intracellular damage and organelle distribution. The cause of producing embryo cytoplsamic fragmentation is not completely understood. Since the fragments have detrimental effects on embryo development, the ultrastructural analysis of fragments may play an important role in fragmentation etiology and in embryo development as well. There are no studies regarding the ultrastructure of fragments in transferable embryos, because the preparation for TEM is not vital and embryos are discarded inevitably. This study aims to introduce a new method for ultrastructural evaluation of fragments without damaging the human cleaving embryos. Microsc. Res. Tech. 79:459–462, 2016 . © 2016 Wiley Periodicals, Inc.